Financial Sustainability of Local Governments: An Analysis of Revenue and Expenditure Bases in Gandaki Province, Nepal - Poudel, Srijana; Rawat, Padam Bahadur (Journal of Multidisciplinary Research Advancements, 2026)
The 2015 Constitution of Nepal created a federal structure with significant revenue and expenditure powers transferred to local governments. However, the financial sustainability of these newly created local governments poses a critical issue. This article examines the revenue and expenditure systems of local governments in Nepal’s Gandaki Province. The research design of this article is descriptive and analytical. The article used both primary and secondary sources of data. The primary data sources used in this article are key informant interviews and structured questionnaires. The secondary data sources used in this article are annual reports, audit reports, and official documents from 27 local governments in Gandaki Province, Nepal. The findings of this article show that local governments have achieved significant milestones in enacting tax laws for conventional revenue sources, such as land revenue and business tax. However, local governments have ignored non-conventional revenue sources. Administrative practices, including automation of the revenue system and budgetary monitoring, are prevalent, but inefficiencies are evident in collection systems: almost three-fourths of municipalities face rising arrears, and almost half face high revenue concentration from a single source. Intergovernmental transfer dependence is high, with 74.1% of all municipalities relying on grants, which form more than half of their total revenue. Large variations are observed in own revenue generation and per capita expenditure among municipalities, indicating fiscal imbalances. The study concludes that, although municipalities have strengthened their fiscal systems, their sustainability is threatened by dependence on grants, inefficiencies in enforcement, and a lack of diversification of revenue, and policy measures should be taken to strengthen the local tax base, collection systems, and link strategic plans with budget execution to achieve the objectives of fiscal federalism in Nepal.